Ask a Statistician: Does Manchester United Really Have 100 Million Followers in China?. Issue 3 (29th May 2019) - Mastrodomenico, Rob
Abstract: A reader writes: I was interested to see a Times article about some new Manchester United-themed centres that will be built in China. In the football club's associated press release, it claims to have "100 million followers" in China. This is, interestingly, 8 million fewer than the figure it claimed to have back in 2012. Is there any truth to these figures?